REGULATION OF EMPLOYMENT IN THE REGION IS AN EXAMPLE OF RUSSIA - Khudoyarov, Rashid; Kosimova, Aziza (Science technology&Digital finance, 2023)
In our scientific article, we study the experiences and methods of various developed countries in regulating employment, assisting it, and reducing the unemployment rate, and we think about achieving good results if we apply these experiences in our country.